PELATIHAN PENYUSUNAN INSTRUMEN ADIKSI GAME PADA SISWA SEKOLAH MENENGAH PERTAMA - Ari Khusumadewi; Retno Tri Hariastuti; Hadi Warsito Wiryosutomo; Zara Diva Paramatatwa (Transformasi dan Inovasi : Jurnal Pengabdian Masyarakat, 2023)
The impact of developments on game technology makes players now able to play online games (online games). The ease of accessing online games and the attractive appearance and model of the game make online games widely played by teenagers to cause addiction. Teenagers at the age of junior high school can play games up to 7 hours a day. With so many junior high school students addicted to games, assistant teachers or junior high school counselors need to be able to develop and use non-test instruments, especially non-game addiction test instruments to address this situation. The training activities are held to provide skills for junior high school counselors or counselors to develop game addiction instruments. The training is carried out for two months by providing intensive and scheduled material and practice. The results of this training are junior high school counselors or counselors who are able to develop their own game addiction instruments and use them to improve guidance and counseling services in schools.